The Pine Branch, March 1923 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1923)
The Pine Branch, March 1923. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1923. Includes: editorials, poems, short stories, and other writings.
An Interlude Page - 1 | Spring Weather Page - 2 | The Verdant Season Page - 9 | The Same Old Way Page - 10 | Reflections of a Senior Page - 13 | Editorial Page - 14 | Locals Page - 16 | Y. W. C. A Page - 17 | Alumnae Page - 19 | Society Notes Page - 21 | Jokes Page - 23 |
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education